Angiographic and optical coherence tomographic results of the MARINA study of ranibizumab in neovascular age-related macular degeneration - Kaiser, Peter K; Blodi, Barbara A; Shapiro, Howard; Acharya, Nisha R (Ophthalmology (Rochester, Minn.), 2007)
To assess pharmacodynamic responses to ranibizumab, an inhibitor of vascular endothelial growth factor A (VEGF-A), in a study of the treatment of minimally classic or occult with no classic choroidal neovascularization secondary to age-related macular degeneration (AMD) (designated MARINA [Minimally Classic/Occult Trial of the Anti-VEGF Antibody Ranibizumab in the Treatment of Neovascular AMD]) and to compare these responses with those in a sham-injection control group. Retrospective (prespecified and ad hoc) analyses of 24-month data. Seven hundred sixteen patients, randomized to 0.3-mg ranibizumab (n = 238), 0.5-mg ranibizumab (n = 240), or a sham injection (n = 238). Stereoscopic fundus photography and fluorescein angiography (FA) were done at baseline and months 3, 6, 12, and 24. Optical coherence tomography (OCT) was performed at a subset of investigative sites (46 patients) at baseline, day 7, and months 1 and 12. Prespecified secondary end points were mean change from baseline in total area of choroidal neovascularization and total area of leakage from choroidal neovascularization at months 12 and 24. Prespecified exploratory FA end points included mean change from baseline in the areas of the choroidal neovascularization lesion and serous sensory retinal detachment (SSRD) at months 12 and 24. Post hoc exploratory FA outcome measures included the proportion of patients with no leakage from choroidal neovascularization and mean change from baseline over time in the area of subretinal fibrous tissue/disciform scar. The prespecified exploratory end point for OCT was mean change from baseline over time in center point thickness. At 12 and 24 months, statistically significant benefits of ranibizumab over sham treatment were observed for mean change from baseline in the areas of choroidal neovascularization lesion, total choroidal neovascularization, leakage from choroidal neovascularization, SSRD, and disciform scar/subretinal fibrosis. At 12 months (final OCT), the mean change in foveal center point thickness on OCT was a significant decrease in the ranibizumab group compared with the sham group. Patients with minimally classic or occult with no classic neovascular AMD treated with ranibizumab demonstrated improvement that was consistent for visual acuity, FA, and OCT outcomes and superior to that in sham-treated patients.